Modulation of sea surface temperature warming in the Bay of Biscay by Loire and Gironde Rivers. Issue 1 (28th January 2016) - Costoya, X.; Fernández‐Nóvoa, D.; deCastro, M.; Santos, F.; Lazure, P.; Gómez‐Gesteira, M.
Abstract: The influence of Loire and Gironde River discharges over the sea surface temperature (SST) in the eastern Bay of Biscay (0.6º–36.6ºW, 44.2º–47.8ºW) was analyzed by means of two complementary databases (MODIS and OISST1/4 ). The area influenced by river plume showed a different SST when compared with the adjacent oceanic area for the months when the plume attains its highest extension (December, January, and February). Ocean was observed to warm at a rate of approximately 0.3ºC dec −1 while temperature at the area influenced by the rivers cooled at a rate of −0.15ºC dec −1 over the period 1982–2014. The mere presence of a freshwater layer is able to modulate the warming observed at adjacent ocean locations since the coastal area is isolated from the rest of the Bay. This nearshore strip is the only part of the Bay where changes in SST depend on North Atlantic Oscillation (NAO) but not on North Atlantic SST represented by the Atlantic Multidecadal Oscillation (AMO). These different cooling‐warming trends are even more patent over the last years (2002–2014) under atmospheric favorable conditions for plume enhancement. River runoff increased at a rate on the order of 120 m 3 s −1 dec −1 over that period and southwesterly winds, which favor the confinement of the plume, showed a positive and significant trend both in duration and intensity. Thus, the coastal strip has been observed to cool at a rate of −0.5°C dec −1 . Key Points: The oceanic area of the Bay warms while the coastal area suffers a cooling The mere presence of a freshwater layer is able to modulate the warming Cooling is reinforced during periods with higher river discharge and SW winds